Evanescent field interaction of tapered fiber with graphene oxide in generation of wide-bandwidth mode-locked pulses. (February 2017) - Ahmad, H.; Faruki, M.J.; Razak, M.Z.A.; Tiu, Z.C.; Ismail, M.F.
Abstract: Pulses with picosecond pulse widths are highly desired for high precision laser applications. A mode-locked pulse laser utilizing evanescent field interaction of a tapered fiber with graphene oxide (GO) is demonstrated. A homemade fabrication stage was used to fabricate the tapered fiber using systematic flame brushing and a GO solution was used to coat the microfiber using optical deposition technique. Pulse trains with a pulse width of 3.46 ps, a 3 dB optical bandwidth of 11.82 nm and a repetition rate of 920 kHz were obtained. The system has substantial potential for many crucial medical, communication, bio processing, military, and industrial applications. Highlights: Fabrication of tappered fiber coated with graphene oxide solution. Details characterization of the tappered fiber with graphene oxide. Wideband mode-locked generation using tappered fiber with graphene oxide.